Chapter 18 - Advances in agrochemical remediation using nanoparticles - Abin Sebastian; Ashwini Nangia; Majeti Narasimha Vara Prasad (Agrochemicals Detection, Treatment and Remediation, 2020)
Agrochemical pollution is a serious threat to environmental safety. Exposure to agrochemicals had deleterious health effects such as nervous system damage and cancer. Biological magnification of persistent agrochemicals also occurred. Hence, remediation approaches for agrochemical pollution must be a holistic approach, including environment and crop produces. The advent of nanotechnology helped to formulate highly efficient methods for the remediation of agrochemicals. High reactive surface area and very small packing space requirements made usage of nanoparticles as a popular agent in agrochemical remediation. Growing interests in surface-engineered nanoparticles promise complete removal of agrochemicals from the environment. Nanosorbents immobilized agrochemicals in the soil and helped microbial degradation of these compounds. However, many of the agrochemicals are persistent, and hence complete removal of these residues practice via photocatalysis. Photocatalytic degradation of persistent agrochemicals using bimetallic nanocomposites widely adopted. Large-scale environmental remediation of agrochemicals in soil, water, and agriculture products achieved via nanoparticles-based agrochemical cleaning systems such as thin-film fixed-bed reactors and nano-phytoremediation.
Keywords: agrochemical cleaning systems; nanosorbents; Pesticides; Photocatalysis; surface engineering